1987
DOI: 10.1210/jcem-65-3-546
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Function in Type II Hyperlipoproteinemic Patients Treated with Lovastatin (Mevinolin) or Neomycin

Abstract: Steroid synthesis requires cholesterol derived from de novo synthesis or plasma lipoproteins. Low density lipoproteins appear to be the major contributor of cholesterol for steroid synthesis in man. Patients with disorders of low density lipoproteins or the low density lipoprotein receptor have reduced cortisol production in response to ACTH. Therapeutic agents designed to lower plasma cholesterol could, therefore, adversely affect steroid hormone production. Lovastatin (mevinolin) is a new hypolipidemic agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 22 publications
4
23
0
Order By: Relevance
“…Results from clinical trials with lovastatin [23, 24| have not shown any adverse effects on hematologic parameters. Sperm counts were not significantly altered by lovastatin therapy [28]. These observa tions provide indirect evidence that tissue lev els of isopentenyl adenine are not adversely affected by therapeutic doses of HMG CoA reductase inhibitors.…”
Section: Isopentenyl Adeninementioning
confidence: 63%
“…Results from clinical trials with lovastatin [23, 24| have not shown any adverse effects on hematologic parameters. Sperm counts were not significantly altered by lovastatin therapy [28]. These observa tions provide indirect evidence that tissue lev els of isopentenyl adenine are not adversely affected by therapeutic doses of HMG CoA reductase inhibitors.…”
Section: Isopentenyl Adeninementioning
confidence: 63%
“…Some studies have shown that the non-absorptive polybasic antibiotic neomycin in vitro induced the precipitation of mixed micelle solution, and in vivo reduced the plasma lipids in type II hyperlipoproteinemia. 21,22 As protamine is a polybasic peptide, we suggest that its lowering lipid effect might be because of the same mechanism as neomycin.…”
Section: Discussionmentioning
confidence: 92%
“…Preclinical studies have shown that serum testosterone and luteinizing hormone levels were not affected by administration of lovastatin, simvastatin or cerivastatin to dogs. In clinical studies, with the exception of a slight decrease in sperm motility, indicators of testicular function (including sperm counts and morphology and serum androgen levels) were not altered in men treated with lovastatin or simvastatin (Farnsworth et al, 1987;Purvis et al, 1992).…”
Section: Testicular Effectsmentioning
confidence: 86%